Cross-cultural aspects of streetscape perception - Rachid Belaroussi; Irène Sitohang; Elena María Díaz González; Jorge Martín-Gutiérrez (Vitruvio: International Journal of Architectural Technology and Sustainability)
Public space auditing is an efficient tool for urban planning of active mobility infrastructures. It enables real estate developers and urban planners to judge the level of comfort their design of sidewalks and public places can provide. Most of the research focus on the methodology to characterize the satisfaction of a public space, but there is a lack of knowledge about inter-cultural aspects of such methods. Our main research question is whether there is consistency in the way in which French and Spanish auditors perceived an urban streetscape: would they rate a public space the same and what features would be differently audited. We selected three urban identities of a modern district representing a variety of urban form: a public place with a tramway station, a commercial street designed as a strip mall, and green residential area with leisure activities. Each of these points of view were audited by a pool of French and Spanish participants according to criteria related to buildings’ architecture and sidewalks’ design for walkability and cyclability purposes. Both virtual reality and real scenes of the public spaces were recorded in videos and provided to participants for rating purposes. Architectural ambiances were measured with qualitative scales, quality of public space was measured with two integrated indicators of pedestrian level of service, and the accordance of infrastructures for active mobility was probed with individual scales. Results from the audit suggest that some streetscape impressions may be quite similar when assessed with various types of measurement, in different cultural contexts: scale, size and architectural style stimulate the same kind of feelings, and the quality of public spaces were perceived equivalently by the two communities as well as bikeability. Dissimilarities in perception occurred for the perception of materials and general feelings of the areas, and in the rating of walkability and in preferences for walking.